Local Current Density and Electrochemical Impedance Measurements within 50 cm Single-Channel PEM Electrolysis Cell. Issue 16 (1st January 2018) - Immerz, C.; Bensmann, B.; Trinke, P.; Suermann, M.; Hanke-Rauschenbach, R.
Abstract : The present analysis shows the local distribution of current density and EIS measurements along a 50 cm single-channel proton exchange membrane water electrolysis (PEMWE) cell. Measurements for operating modes with one sufficiently high and one insufficiently low stoichiometric water ratio (λ) were carried out to observe effects on the current density distribution. Furthermore, global and local EIS measurements were performed to distinguish between the cell voltage loss differences in the two cases. The mass transport losses ηmtx and the Ohmic voltage losses ηΩ show a strong increase, when the stoichiometric water ratio falls below a level of λ ≈ 5. The reduction of the inlet water flux of the anode reduces both the proton conductivity of the ionomer within the catalyst layer and the membrane, increasing transport and Ohmic resistances, respectively. The local analysis has shown that the level of membrane and catalyst hydration under low stoichiometric conditions can be distributed highly non-homogeneous in along-the-channel direction, with the most pronounced dehydration toward the end of the channel.